Zambia Water Supply and Sanitation Sector Diagnostic : Narrowing the Gap between Policy and Practice - World Bank (World Bank, Washington, DC, 2020)
Access to water supply and sanitation (WSS) services remains stubbornly low in Zambia. This poor record on WSS service delivery is disastrous for Zambia’s economy by negatively affecting human capital development, which in turn creates a drag on the economy. Successive governments in Zambia have recognized this important sector of the economy and launched reforms and investment programs. Successive governments in Zambia have recognized this important sector of the economy and launched reforms and investment programs. This analysis shows that Zambia’s chronically inefficient water utilities are creating a fiscal burden and making it harder for the government to finance the sector. The rest of the report is organized as follows: Chapter 2 provides an analysis of the strategic relevance of the WSS programs to Zambia’s economy, drawing on existing literature on the economic impacts of WSS and analysis of a sample of projects in both programs. Chapter 3 analyzes the extent to which the programs are structured to deliver desired results, focusing on the design and prioritization of investments, implementation arrangements, and monitoring and evaluation. Chapter 4 provides an analysis of the expenditure framework for both programs and the extent to which it supports efficient program implementation. Chapter 5 summarizes opportunities that exist to enhance the effectiveness and impact of both programs and makes recommendations on medium-term actions to advance Zambia’s WSS sector and narrow the gap between policy and practice.